MAKAM GEDIBRAH: TINJAUAN NILAI-NILAI SEJARAH DALAM PERSPEKTIF FOLKLOR - Onok Yayang Pamungkas; Ibrahim Abdillah (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2021)
This study used descriptive qualitative research methods to obtain a descriptive study of folklore and symbolic meaning. While the research strategy used in this study is ethnographic research to obtain a description of the historical values at the Gedibrah Tomb and data collection is carried out by in-depth interviews and participant observation. Gedibrah grave is located in Tambakagung Village, Klirong District, Kebumen Regency, Central Java province. It is located in the middle of rice fields. The grave is known by local residents for its historical value so that the Gedibrah grave is one of the historical icons in Tambakagung Village, Klirong District and the community in several nearby villages. In this study, the folklore that is raised is the historical values that exist in the Gedibrah grave, Tambakagung Village, Klirong District. The nuances of culture are still be highlighted around the grave. The choice of this topic because it is quite popular and well known in the surrounding local community. The need for this research is to understand and interpret the historical value in the Gedibrah grave. To capture this value, it is also necessary to understand the culture at the time the story was made. Based on the results of the research, and the folklore which as a part of folklore has long lived in the community in certain areas, including in Tambakagung Village, Klirong District, Kebumen Regency, it has been spread orally from one generation to the next generation hereditary. Keywords: Grave, Gedibrah grave, Tambakagung Village.